2016
DOI: 10.19173/irrodl.v17i4.2370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Group Awareness and Self-Regulation Level on Online Learning Behaviors

Abstract: Group awareness can affect student online learning while self-regulation also can substantially influence student online learning. Although some studies identify that these two variables may partially determine learning behavior, few empirical studies or thorough analyses elucidate the simultaneous impact of these two variables (group awareness and self-regulation) on online learning behavior. This paper compared one online collaboration environments with GA support with one without group awareness (NA) suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Compared with the low‐SRL students, the high‐SRL students are more prepared before class because they spend more time on material review and better scores on personal uploaded Excel and IRAT. This result echoes some literatures that high‐SR learners tend to play active roles in learning, taking responsibility, and being persistent for their own learning (Lin et al, ; Lin & Lai, ; Wang, ). Additionally, the peer evaluation feedback indicated that the high‐SRL students received higher credits than the low‐SRL students did for all items (“Preparation,” “Contribution,” “Gatekeeping,” “Flexibility,” and “Overall”).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Compared with the low‐SRL students, the high‐SRL students are more prepared before class because they spend more time on material review and better scores on personal uploaded Excel and IRAT. This result echoes some literatures that high‐SR learners tend to play active roles in learning, taking responsibility, and being persistent for their own learning (Lin et al, ; Lin & Lai, ; Wang, ). Additionally, the peer evaluation feedback indicated that the high‐SRL students received higher credits than the low‐SRL students did for all items (“Preparation,” “Contribution,” “Gatekeeping,” “Flexibility,” and “Overall”).…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, some studies stress that SRL ability should be discussed in the context of social (peer) groups, particular in collaborative environments (Lin, ; Yowell & Smylie, ). This is because from the prospective of social cognitive theory, SRL ability is based both on individual (intrapsychological) and on social (interpersonal) processes (Lin, ; Lin, Szu, & Lai, ). In other words, SRL ability is also influenced by social (or peer) context and interaction (Lin, ; Panadero & Järvelä, ; Zimmerman, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin, Huang, and Chuang (2015) found that SR interferes with the learning behaviour and efficiency of students with varying network centrality (i.e., students with high network centrality have the most close friends within a community) in a computer-supported collaborative learning (CSCL) environment. Lin, Szu, and Lai (2016) also found that the learning behaviour of students in different CSCL systems (i.e., a system that provides the context of peer interaction back to a student versus a system without such support) depends on their SR levels. In sum, although students with different SR levels differ in their learning motivation, behaviour, and performance in e-learning environments, few studies have investigated how SR levels affect e-learning (CBA) user acceptance.…”
Section: Moderating Effects Of Self-regulation (Sr) Levels On Cba's Umentioning
confidence: 95%
“…Employing this data will also allow students to coordinate the content space, as well as the relational space of collaboration ). If such tools are employed in the context of a collaborative web environment, then they will provide students with information about the learning interaction or the knowledge of their peers (or of group members), which will, in turn, implicitly guide the behavior, communication, and reflection of the students (Kimmerle & Cress, 2008;Lin, Szu & Lai, 2016). It should be noted at this point that awareness tools usually process information by, first, evaluating all relevant information, then transforming it, and, finally, by channeling it back to the learners in a way they find suitable, using visual prompts or other means (Buder and Bodemer, 2008).…”
Section: Monitoring Awareness and Reflectionmentioning
confidence: 99%